(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
The polycystic ovarian syndrome is the leading cause of female infertility in the present scenario. It is one of the top reproductive endocrine disorders in the world. In the conventional method, no definite treatment is proven for this ailment and it mainly depends upon hormonal preparations and invasive techniques. These modalities are costlier and have many side effects. In Polycystic ovarian syndrome, there isNashtarthava which means the loss of ovulation as well as menstruation. Kapha Vatha Avarana causing Artavanasha which is explained as Nashtarthava by Susrutha can also be considered in this particular disease. Vatha is the cardinal Dosha vitiated in all these conditions. So the treatment modalities which correct Vathavaigunya can be adopted here. By considering the above facts Snehana with Pippalyadi anuvasana thaila and Virechana with Hingutriguna thaila were selected. These treatment modalities help in correcting Mootavatha and thereby removing Arthavavaha srothorodha. The study design was a pre and post interventional study with a sample size of 30. Females in the age group 18-38 years with Polycystic Ovarian syndrome attending the outpatient and inpatient department of Govt Ayurveda College hospital for women and children Poojappura, was selected for study as per Rotterdam Criteria. The symptoms were assessed before starting treatment using a case proforma, ultra-sonogram, and necessary lab investigations. The assessment was done each month during the study period and the follow-up period. Data obtained was analyzed statistically. The treatment was found to be effective in normalizing menstrual intervals, reducing the volume of ovaries, and reducing the body mass index. It was not effective in reducing the number of follicular cysts and in the induction of ovulation within the study period.